STRATEGI PENGKADERAN IPNU IPPNU KABUPATEN LUMAJANG DALAM MENGHADAPI DISRUPSI DIGITAL DAN TANTANGAN GENERASI Z - Mochammad Faisal Murad; Bambang Subahri (Smart Education, 2026)
Abstract: This study aims to describe and analyze the cadre development strategies implemented by the Branch Leadership (PC) of IPNU IPPNU Lumajang Regency in facing the era of digital disruption and the unique characteristics of Generation Z. As the largest mass-based student organization, IPNU IPPNU is faced with the challenge of declining interest in conventional organizations due to the shift to digital lifestyles. The research method used is descriptive qualitative, with data collection techniques through in-depth interviews, media observation, and documentation. The results show that PC IPNU IPPNU Lumajang has transformed its cadre development through three main channels: (1) Innovation in recruitment media based on creative content on the TikTok and Instagram platforms, (2) Adaptation of formal cadre development materials that are more interactive and relevant to current Gen-Z issues, and (3) Utilization of communication technology for organizational management at the PAC and Branch levels. The main supporting factor is the availability of digitally competent human resources, but this is hampered by the gap in technology access in several geographic areas of Lumajang Regency. This study concludes that hybrid cadre development (a combination of physical and digital) is an effective solution for maintaining the organization's existence in the era of disruption. Keywords: Cadre Development, IPNU IPPNU, Lumajang, Digital Disruption, Generation Z. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis strategi pengkaderan yang diterapkan oleh Pimpinan Cabang (PC) IPNU IPPNU Kabupaten Lumajang dalam menghadapi era disrupsi digital dan karakteristik unik Generasi Z. Sebagai organisasi pelajar berbasis massa terbesar, IPNU IPPNU dihadapkan pada tantangan penurunan minat organisasi secara konvensional akibat pergeseran gaya hidup digital. Metode penelitian yang digunakan adalah kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara mendalam, observasi media, dan dokumentasi. Hasil penelitian menunjukkan bahwa PC IPNU IPPNU Lumajang melakukan transformasi pengkaderan melalui tiga jalur utama: (1) Inovasi media rekrutmen berbasis konten kreatif di platform TikTok dan Instagram, (2) Adaptasi materi kaderisasi formal yang lebih interaktif dan relevan dengan isu-isu terkini Gen-Z, serta (3) Pemanfaatan teknologi komunikasi untuk manajemen organisasi di tingkat PAC hingga Ranting. Faktor pendukung utama adalah ketersediaan sumber daya manusia yang cakap digital, namun terkendala oleh kesenjangan akses teknologi di beberapa wilayah geografis Kabupaten Lumajang. Penelitian ini menyimpulkan bahwa pengkaderan hibrida (gabungan fisik dan digital) menjadi solusi efektif dalam menjaga eksistensi organisasi di era disrupsi. Kata Kunci : Kaderisasi, IPNU IPPNU, Lumajang, Disrupsi Digital, Generasi Z.